2014
DOI: 10.1016/j.najef.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Do stock markets discipline US Bank Holding Companies: Just monitoring, or also influencing?

Abstract: General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the public portal for the purpose of private study or research-You may not further distribute the material or use it for any profit-making activity or commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
0
4
1
Order By: Relevance
“…It also conforms to the findings of Flannery (2001), who found no evidence of EH's influence or bondholders' monitoring of bank indicators. However, our finding contradicts the study by Baele et al (2014) on EHs' discipline. These authors found evidence for banks' reaction to market signals, as banks had swelled their long-term target capital and reduced their liquidity risk in response to these signals.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…It also conforms to the findings of Flannery (2001), who found no evidence of EH's influence or bondholders' monitoring of bank indicators. However, our finding contradicts the study by Baele et al (2014) on EHs' discipline. These authors found evidence for banks' reaction to market signals, as banks had swelled their long-term target capital and reduced their liquidity risk in response to these signals.…”
Section: Discussioncontrasting
confidence: 99%
“…Jones et al (2013) found that banks imposed elevated returns rates on opaque investments, elevating systematic risk. Baele et al (2014) showed that EHs use the accounting information disclosed in banks' financial statements to assess banks' valuation and risk. Investors' valuations of banks were measured by the market-to-book ratio and the semi-volatility.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The market discipline would be more efficient if the price of bank liabilities correctly incorporates full and qualitative information of bank credit risks proprieties, and then reflects the fair yield for risks (Ellis & Flannery, 1992). There exists a large literature on the market discipline in the banking literature, most of them however focus on the bank risk-taking behaviours without final conclusions (Bliss, 2004;Bliss & Flannery, 2002;Ashcraft, 2008;Baele et al, 2014;among others).…”
Section: Introductionmentioning
confidence: 99%